Mengintip Dunia Bisnis Bersama Para Profesional Muda Novel Sang Profesional Karya Tikno Iensufiie - Novia Ramah Safitri; Renelyn I. Reyes; Evi Dwi Kurniawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to describe the form of peering into the business world with young professionals in the novel The Professional. Before discussing in more depth, we must know the meaning of business? What are the goals and what theories are included in the business world? Business is an activity in which a person or group of people makes, sells, or exchanges goods or services with the aim of making a profit. The goals of business are to increase economic growth in society in general, create jobs, maintain the existence of the company in the long term, meet life's needs with products and services, and provide prosperity for owners of production factors and society. Theories that are often used in the business world are, business decision on investment theory, return on investment and return on assets, cash flow quadrant, law of diminishing returns on practice, negotiation rules, and balanced scorecard on efficiency. Well, these theories are theories tucked away in professional novels which are explained or described in fictional language that is easy for readers to understand.